A Novel Combined Use of Dupilumab for Treatment of Aggressive Refractory Pemphigus Vulgaris Complicated With Pulmonary Tuberculosis: A Case Report and the RNA-seq Analysis - Chen, Siji; Zhan, Shaowei; Hua, Chunting; Tang, Yi; Cheng, Hao (Frontiers in Immunology, 2022)
Background Pemphigus vulgaris (PV) is a kind of IgG-mediated autoimmune blistering disease (AIBD) that is characterized by loss of keratinocyte adhesion in the epithelium of mucous membranes or skin. Recently, pemphigus vulgaris was thought to be associated with classical T helper 2 (TH2)-type cytokines such as interleukin‐4 (IL-4) and interleukin‐17 (IL-17) signaling pathway. A humanized monoclonal IgG4 antibody called dupilumab binds to the alpha subunit of the interleukin‐4 receptor (IL‐4Rα) and inhibits the signaling of IL-4 and interleukin‐13 (IL-13), which has been successfully applied for atopic dermatitis and asthma. Currently, the clinical trial evaluating dupilumab in bullous pemphigoid is ongoing. Objective To determine whether dupilumab may be of benefit in the aggressive refractory pemphigus vulgaris. Methods We report a 35-year old male with refractory pemphigus vulgaris and pulmonary tuberculosis who received treatment with dupilumab for 10 weeks. The mRNA expression of peripheral blood mononuclear cells (PBMCs) was analyzed by RNA sequencing (RNA-seq) which showed the gene expression changes after treatment. Results The skin lesions of the patient improved in response to the combined use of dupilumab, moderate dose of glucocorticosteroids, and intravenous immune globulin (IVIG). Downregulations of inflammatory response-related genes and IL-17 signaling pathway-related genes were observed in PBMCs. Conclusion We describe a patient with refractory pemphigus vulgaris and pulmonary tuberculosis who had the disease under control with combined use of dupilumab as an add-on treatment. Dupilumab may provide a beneficial effect in aggressive refractory pemphigus vulgaris.